Brain and skeletal muscle bioenergetic failure in familial hypobetalipoproteinaemia. Issue 6 (June 1997) - Lodi, R; Rinaldi, R; Gaddi, A; Iotti, S; D'Alessandro, R; Scoz, N; Battino, M; Carelli, V; Azzimondi, G; Zaniol, P; Barbiroli, B
Abstract : OBJECTIVE: To determine whether a multisystemic bioenergetic deficit is an underlying feature of familial hypobetalipoproteinaemia. METHODS: Brain and skeletal muscle bioenergetics were studied by in vivo phosphorus MR spectroscopy (31P-MRS) in two neurologically affected members (mother and son) and in one asymptomatic member (daughter) of a kindred with familial hypobetalipoproteinaemia. Plasma concentrations of vitamin E and coenzyme Q10 (CoQ10) were also assessed. RESULTS: Brain 31P-MRS disclosed in all patients a reduced phosphocreatine (PCr) concentration whereas the calculated ADP concentration was increased. Brain phosphorylation potential was reduced in the members by about 40%. Skeletal muscle was studied at rest in the three members and during aerobic exercise and recovery in the son and daughter. Only the mother showed an impaired mitochondrial function at rest. Both son and daughter showed an increased end exercise ADP concentration whereas the rates of postexercise recovery of PCr and ADP were slow in the daughter. The rate of inorganic phosphate recovery was reduced in both cases. Plasma concentration of vitamin E and CoQ10 was below the normal range in all members. CONCLUSIONS: Structural changes in mitochondrial membranes and deficit of vitamin E together with reduced availability of CoQ10 can be responsible for the multisystemic bioenergetic deficit. Present findings suggest that CoQ10 supplementation may be important in familial hypobetalipoproteinaemia.